Project : workbook. (Oxford : University Press, 2008)
Project third edition encourages students to enjoy the process of learning, through updated content and a wealth of materials. It motivates students with engaging texts, topics, and activities across all five levels. The logical structure and clear approach provide a solid base for learning, as the course presents real language in real contexts. Expanded culture and revision sections in the new edition provide additional activities and practice for students, and further resources for teachers.
2
Keywords: Engels -- Secundair onderwijs